Dalla formalizzazione della metapsicologia alla naturalizzazione della matematica - Lami, Gabriele (Metapsychologica - rivista di psicanalisi freudiana, 2023)
When reviewing metapsychology to assess its aptness to mathematical formalism, one encounters objects akin to the typical objects of mathematics. Given the different roots of metapsychology and mathematics, this analogy is worth investigating, in order to highlight structures that potentially do not quite belong to either discipline, but rather reflect the very structure of the mind. This article seeks to open up avenues that help to identify these similarities, based on examples from the two disciplines.